Sintaxe da Língua Portuguesa na segunda metade do século XIX: o Complemento Nominal sob uma abordagem historiográfica - Almeida, Wemylla de Jesus (2019)
This research makes a reflection about the syntax of the Portuguese Language, especially, the Complement Nominal, in Brazil, in the second half of the nineteenth century. For that, we take as corpus the work of grammar study: Syntax and construction of Lingua Portugueza, by Thomaz da Silva Brandão (1888). Thus, we are based on Linguistic Historiography (HL), specifically with Koerner (1996), following its three principles, namely: Contextualization, which traces the mood of opinion, the spirit of the time; Immanence, which establishes a general framework of theory and terminology used in works; Adequacy, which introduces modern approaches to technical vocabulary. Thus, for the appropriateness, we made use of the work of grammar study: New Lessons of Syntactic Analysis, by Adriano da Gama Kury (1999). In view of this, our main objectives are to explain how the study of the syntax, especially the Nominal Complement, for the Portuguese Language implementation process, in the second half of the nineteenth century, in addition to explaining the process of implementing a linguistic policy under a historiographic approach. With the results achieved, we verified that the works analyzed brought great contributions because they deal with an innovative approach on the Nominal Complement, so that they led to essential reflections to the study of the Syntax of the Portuguese Language in Brazil, thus filling some existing syntactic gaps